Proceedings of the 17 Th International Symposium on Management (INSYMA 2020) 2020
DOI: 10.2991/aebmr.k.200127.026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities for SME’s: Ready to Change and Cloud Service Role Toward Digital Business

Abstract: The digital age is an exciting era for technology and business. In this era, all business sectors change from manual to digitalization in their operations, including the Small Medium Enterprises (SMEs). Digitalization is required to survive and sustainable competitive advantages. The biggest challenge being faced by SMEs is how to increase the accessibility of SMEs to go digital and improve the capabilities of SMEs, so their products can compete with foreign products. In Indonesia, some SME players already app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the digitalization era, digital technology in marketing practice can replace intuition, experience, theory, and brands to generate innovative customize products and optimize promotions on real-time bases of individual consumers (Cluley et al, 2019). The integration of data in marketing practice offers many benefits to the decision-making process (Cluley et al, 2019), forming customer knowledge management strategies and the dynamic ability to face the turbulence of the current business environment (Francesco et al, 2020;Suhendi et al, 2020). In addition, the adoption of technology in marketing practices and human resources concern on marketing skills, customers' social communication, and customer relationship management must be maintained well to assure the sustainability of SMEs in competitive advantages (Kotler, 2001;Adam et al, 2020).…”
Section: Marketing (Mc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the digitalization era, digital technology in marketing practice can replace intuition, experience, theory, and brands to generate innovative customize products and optimize promotions on real-time bases of individual consumers (Cluley et al, 2019). The integration of data in marketing practice offers many benefits to the decision-making process (Cluley et al, 2019), forming customer knowledge management strategies and the dynamic ability to face the turbulence of the current business environment (Francesco et al, 2020;Suhendi et al, 2020). In addition, the adoption of technology in marketing practices and human resources concern on marketing skills, customers' social communication, and customer relationship management must be maintained well to assure the sustainability of SMEs in competitive advantages (Kotler, 2001;Adam et al, 2020).…”
Section: Marketing (Mc)mentioning
confidence: 99%
“…The technical infrastructure is explained as SMEs' readiness through the availability of IT infrastructure, hardware, and software in bolstering digitalization (Budhiraja, 2019;Al-Balushi et al, 2014;Suhendi et al, 2020). Time access and technical infrastructure usage are also discussed as considered factors in this dimension (Hooi, 2006;De Carolis, 2017;Hanafizadeh, P. et al, 2009).…”
Section: The Technical Infrastructurementioning
confidence: 99%
“…Companies must apply dynamic capability to adapt to existing changes so that MSMEs' performance will be better (Hernández-Linares et al, 2020) and create new value (Adeniran and Johnston, 2016;Oliva et al, 2019) (Oliva et al, 2019). Suhendi et al, (2020) suggested that the higher the level of individual readiness to change, the higher the dynamic capability in each organization. On the other hand, Drnevich and Kriauciunas…”
Section: Introductionmentioning
confidence: 99%